A halo blue straggler on a highly eccentric retrograde orbit - Tillich, A.; Przybilla, Norbert; Scholz, R. -D.; Heber, Ulrich (Astronomy & Astrophysics, 2010)
Context. Blue stragglers, which are stars that appear to be younger than they should be, are an important population of unusual stars in both stellar clusters and the halo field of the Galaxy. Most formation scenarios evoke either stellar collisions or binary stars that transfer mass or merge. Aims. We investigate high-velocity stars in the Galactic halo and perform a spectral and kinematical analysis to shed light on their nature and origin. Here we report that SDSSJ130005.62+042201.6 (J1300+0422 for short) is an A-type star of unusually large radial velocity (504.6 ± 5 km s-1). Methods. From a quantitative NLTE (and LTE) spectral analysis of medium-resolution optical spectra, the elemental composition is derived. Proper motion measurements combined with a spectroscopic distance estimate allow us to determine its present space velocity. Its kinematical properties are derived by integrating the equation of motion in the Galactic potential. Results. We find J1300+0422 to be metal poor ([M/H]=-1.2) and exhibit an α-element enrichment (0.3-0.4 dex) that is characteristic of the halo population, as confirmed by a kinematical analysis of its 3D space motions, which places it on a highly eccentric retrograde Galactic orbit. Conclusions. The mass of J1300+0422 (1.15 ± 0.10 &Modot) is higher than the globular cluster turn-off masses indicating that it is a halo blue straggler star. At a Galactic rest-frame velocity of ≈467 km s-1, the star travels faster than any known blue straggler but is still bound to the Galaxy. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Blue stragglers; Galaxy: halo; Stars: atmospheres; Stars: individual: SDSSJ130005.62+042201.6; Stars: kinematics and dynamics; Stars: Population II

HIP 60350: A supernova ejected hyper-runaway star? - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Proceedings of Science, 2010)
Halo runaway stars, i.e., young, massive, high-velocity stars in the halo of our Galaxy, are widely supposed to be the result of an ejection event from the Galactic disk. The three most likely ejection scenarios are tidal disruptions of binary systems by the supermassive black hole at the Galactic center, dynamical interactions in star clusters, e.g., binary-binary encounters, or a supernova explosion disrupting a binary system. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to discuss the three competing mechanisms. Using spectrum synthesis techniques that allow for deviations from local thermal equilibrium, we derived chemical elemental abundances from high resolution spectra. The analysis of HIP 60350 revealed an outstanding high Galactic rest-frame velocity of 530±35kms-1 slightly exceeding the local Galactic escape velocity and thus qualifying the star as a hyper-runaway candidate, i.e., an unbound runaway star. The kinematically predicted birthplace within the disk is located ∼ 6kpc away from the Galactic center excluding this region as the star's spatial origin and in this way the involvement of the central supermassive black hole. Instead, the obtained chemical abundance pattern shows hints of α-element enhancement being characteristic of supernova debris. HIP 60350 might be the surviving secondary of a massive, close binary system disrupted by the primary's supernova explosion. © Copyright owned by the author(s).
CRIS-Team Scopus Importer:2020-12-21

On the He-3 anomaly in hot subdwarf B stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Nieva, M. F.; Przybilla, Norbert (SCIENDO, 2017)
Decades ago, He-3 isotope enrichment in helium-weak B-type main-sequence, in blue horizontal branch and in hot subdwarf B (sdB) stars, i.e., helium-core burning stars of the extreme horizontal branch, were discovered. Diffusion processes in the atmosphere of these stars lead to the observed abundance anomalies. Quantitative spectral analyses of high-resolution spectra to derive photospheric isotopic helium abundance ratios for known He-3 sdBs have not been performed yet. We present preliminary results of high-resolution and high S/N spectra to determine the He-3 and He-4 abundances of nine known He-3 sdBs. We used a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars investigating multiple He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which show the strongest isotopic shifts in the optical spectral range. We also report the discovery of four new He-3 sdBs from the ESO Supernova Progenitor survey. Most of the He-3 sdBs cluster in a narrow temperature strip between similar to 26000 K and similar to 30000 K and have almost no atmospheric He-4 at all. Interestingly, three He-3 sdBs show evidence for vertical helium stratification.
Keywords: Stars: chemically peculiar; Stars: atmospheres; Stars: fundamental parameters; Stars: abundances; subdwarfs; Stars: horizontal-branch

The nature of the hyper-runaway candidate HIP60350 - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Astrophysical Journal, 2010)
Young, massive stars in the Galactic halo are widely supposed to be the result of an ejection event from the Galactic disk forcing some stars to leave their place of birth as so-called runaway stars. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to determine which runaway scenario - a supernova explosion disrupting a binary system or dynamical interaction in star clusters - may be responsible for HIP 60350's peculiar orbit. Based on a non-local thermodynamic equilibrium approach, a high-resolution optical echelle spectrum was examined to revise spectroscopic quantities and for the first time to perform a differential chemical abundance analysis with respect to the B-type star 18 Peg. The results together with proper motions from the Hipparcos Catalog further allowed the three-dimensional kinematics of the star to be studied numerically. The abundances derived for HIP 60350 are consistent with a slightly supersolar metallicity agreeing with the kinematically predicted place of birth ∼6 kpc away from the Galactic center. However, they do not exclude the possibility of an α-enhanced abundance pattern expected in the case of the supernova scenario. Its outstanding high Galactic rest-frame velocity of 530 ± 35 km s-1 is a consequence of ejection in the direction of Galactic rotation and slightly exceeds the local Galactic escape velocity in a standard Galactic potential. Hence, HIP 60350 may be unbound to the Galaxy. © 2010. The American Astronomical Society.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Stars: abundances; Stars: atmospheres; Stars: distances; Stars: early-type; Stars: individual (HIP 60350; 18 Peg); Stars: kinematics and dynamics

Weighing the galactic dark matter halo: A lower mass limit from the fastest halo star known - Przybilla, Norbert; Tillich, Alfred; Heber, Ulrich; Scholz, Ralf-Dieter (Astrophysical Journal, 2010)
The mass of the Galactic dark matter halo is under vivid discussion. A recent study by Xue et al. revised the Galactic halo mass downward by a factor of ∼2 relative to previous work, based on the line-of-sight velocity distribution of ∼2400 blue horizontal-branch (BHB) halo stars. The observations were interpreted with a statistical approach using cosmological galaxy formation simulations, as only four of the six-dimensional phase-space coordinates were determined. Here we concentrate on a close investigation of the stars with the highest negative radial velocity from that sample. For one star, SDSSJ153935.67+023909.8 (J1539+0239 for short), we succeed in measuring a significant proper motion, i.e., full phase-space information is obtained. We confirm the star to be a Population II BHB star from an independent quantitative analysis of the Sloan Digital Sky Survey (SDSS) spectrum - providing the first non-LTE (NLTE) study of any halo BHB star - and reconstruct its three-dimensional trajectory in the Galactic potential. J1539+0239 turns out to be the fastest halo star known to date, with a Galactic rest-frame velocity of 694+300-221 km s-1 (full uncertainty range from Monte Carlo error propagation) at its current position. The extreme kinematics of the star allows a significant lower limit to be put on the halo mass in order to keep it bound, of Mhalo ≥ 1.7+2.3-1.1 × 1012 M⊙. We conclude that the Xue et al. results tend to underestimate the true halo mass as their most likely mass value is consistent with our analysis only at a level of 4%. However, our result confirms other studies that make use of the full phase-space information.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Dark matter; Galaxy: halo; Stars: atmospheres; Stars: horizontal-branch; Stars: kinematics and dynamics; Stars: Population II